Percutaneous Closure of Ruptured Sinus of Valsalva Aneurysm in a Child Using a Patent Ductus Arteriosus Device. Issue 1 (January 2023) - Peirone, Alejandro; Contreras, Alejandro; Guevara, Antonio; Allub, Alejandro; Bueno, Nora; Banille, Edgardo; Díaz, Juan; Juaneda, Ignacio
Ruptured sinus of Valsalva aneurysm is rare, although if left untreated, potentially fatal disease. Surgical approach has been the main treatment in most series; nevertheless, percutaneous closure has been described in selected cases. We report a 5-year-old boy presenting with rapid clinical deterioration who underwent percutaneous closure using a patent ductus arteriosus device, with the resolution of symptoms. Descriptions of this technique being utilized in children are infrequent in the literature.